The Legal Position of the Indonesian Ulema Council in Applying the Principles of Islamic Law in Islamic Banking Operations in Indonesia - Try Widiyono (International Journal Labs, 2024)
National economic development through the establishment of Islamic Banks is an implementation of Article 29 of the 1945 Constitution of the Republic of Indonesia. The presence of Islamic Banking in the national economy is a strategic legal policy of the government because its operations are based on the principles of Islamic law, namely principles derived from the Qur'an, Hadith, Ijma', and Qiyas. However, in its application, these principles of Islamic law are manifested in the form of fatwas issued by the National Sharia Council-Indonesian Ulema Council (DSN-MUI) as a source of positive law for Islamic banking. Therefore, this study raises legal issues related to the legal position of the Indonesian Ulema Council in the application of sharia principles to Islamic Banking operations in Indonesia. This study aims to analyze and determine the legal position of the Indonesian Ulema Council in the application of sharia principles to Islamic Banking in Indonesia. The research method used is normative research, which provides answers to the problems raised with the perspective of what should be done. The results of the study indicate that the DSN-MUI fatwa has a crucial role as a positive legal basis in the operation of Islamic Banking in Indonesia, although formally it is not a statutory regulation. The implications of this study indicate the importance of recognizing and strengthening the role of the DSN-MUI in the national legal system to ensure compliance of Islamic Banking operations with applicable sharia principles.